Predictors of Young People’s Career Intentions as Islamic Bankers - Amin, Hanudin (Universitas Muhammadiyah Yogyakarta, 2020)
Understanding the willingness of university students pursuing their career as Islamic bankers has proven to be one of the most challenging research topics in the Islamic banking field. This study examines the factors affecting the career intentions as Islamic bankers among university students in Malaysia. Drawing upon Decomposed Theory of Planned Behavior (DTPB), this study examined the factors determining the students' willingness to become Islamic bankers as their future job. Our analysis is based on the 350 respondents involved. Results obtained show that all factors are examined were instrumental in determining the career intentions as Islamic bankers. Our findings should be interpreted with caution. We identified two limitations, first is on the use of the university students as proxies and second our data which was confined to Islamic finance program whilst neglecting other students from business and finance disciplines. The results help improve the role of bank managers to provide proper packages of training to improve the students’ confident to become future Islamic bankers. Besides, this study extends the DTPB’s applicability to include career intentions as Islamic bankers in a Malaysia context.